Hepatocyte polarization is essential for the productive entry of the hepatitis B virus - Schulze, Andreas; Urban, Stephan (Hepatology, 2011)
Abstract Human hepatitis B virus (HBV) is characterized by a high species specificity and a distinct liver tropism. Within the liver, HBV replication occurs in differentiated and polarized hepatocytes. Accordingly, the in vitro HBV infection of primary human hepatocytes (PHHs) and the human hepatoma cell line, HepaRG, is restricted to differentiated, hepatocyte?like cells. Though preparations of PHH contain up to 100% hepatic cells, cultures of differentiated HepaRG cells are a mixture of hepatocyte?like and biliary?like epithelial cells. We used PHH and HepaRG cells and compared the influence of virus inoculation dose, cell differentiation, and polarization on productive HBV infection. At multiplicities of genome equivalents (mge) >8,000, almost 100% of PHHs could be infected. In contrast, only a subset of HepaRG cells stained positive for HBcAg at comparable or even higher mge. Infection predominantly occurred at the edges of islands of hepatocyte?like HepaRG cells. This indicates a limited accessibility of the HBV receptor, possibly as a result of its polar sorting. Multidrug resistance protein 2 (MRP2), a marker selectively transported to the apical (i.e., canalicular) cell membrane, revealed two polarization phenotypes of HepaRG cells. HBV infection within the islands of hepatocyte?like HepaRG cells preferentially occurred in cells that resemble PHH, exhibiting canalicular structures. However, disruption of cell?cell junctions allowed the additional infection of cells that do not display a PHH?like polarization. Conclusion: HBV enters hepatocytes via the basolateral membrane. This model, at least partially, explains the difference of PHH and HepaRG cells in infection efficacy, provides insights into natural HBV infection, and establishes a basis for optimization of the HepaRG infection system. (HEPATOLOGY 2012)